Digital Marketing Management in improving Business Performance: Study on Bank Jateng Syariah - daniarso, Indra; Hendri hermawan (Velocity: Journal of Sharia Finance and Banking, 2024)
This study aims to analyze the use of Instagram as a marketing tool in promoting Bank Jateng Syariah funding and financing products, as well as marketing strategies and their influence on improving the Bank's business performance. The research method used is qualitative with a descriptive approach. Data is collected through literature study and analysis of social media analytics from Instagram posts. The results showed that Bank Jateng Syariah successfully used Social Media as a marketing tool by presenting interesting and informative visual content regarding the distribution of funds and financing programs. The marketing strategy involves active interaction with the audience, and utilization of social media features. Promotion of Bank Jateng Mobile Banking application also has a positive impact on increasing awareness, downloads, and use of digital banking services.